JINGLE AND CHALLENGE EVENTS FOR HAWAI WATERPARK MALANG - Agung Wijaya; Evan Kartika; Lia Kartika (AIBPM Publisher, 2018)
Hawai Waterpark Malang is waterpark which is located in Malang City, Hawai Waterpark Malanghas advantages offered as a first waterpark in Malang City that has Tsunami Rides. Hawai Waterpark Malang hope that visitingcan add closeness to family relationships. Therefore,HawaiWaterpark Malang has a lot of events and rides that can be played together and enjoyed comfortably. for in this poor city itself the existence of waterpark just a little so Hawai waterpark is a waterpark with good service and has a variety of interesting rides as well. HawaiWaterpark Malang already use social media including Google, Youtube, Facebook and official website for marketing promotions. how to promote hawai place by uploading new video on youtube videos and hold important events that fit with date like hallowen party. The problem isHawai Waterpark Malang still lack of human resourceswho can speak English fluently, so the promotion is done so far still using the Indonesian language. For the reason that foreigners did not catch the message conveyed through Hawai Waterpark promotionand not many foreigners who visited Hawai Waterpark Malang. The idea that team 20 gave to Hawai Waterpark Malang was to hold a jingle race and challenge event. The purpose of this idea is to improve the branding of Hawaii Waterpark Malang, attract foreigners to participate in the event and come to Hawaii Waterpark water park Malang. In executing the idea of the jingle race and challenge event, team 20 will work with travel agents in China, Malaysia, Singapore and Australia. This cooperation aims to make Hawaii Waterpark Malang as one of the tourist destinations in the tour packages of these agents.